Efektivitas Undang-Undang Hak Cipta Dalam Menanggulangi Penyebaran Spoiler Film Di Media Sosial Tiktok: Studi Kasus Film Mencuri Raden Saleh - Yaumil, Syahrul; Nahrowi, Nahrowi (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2024)
The effectiveness of the Copyright Law in dealing with the practice of spreading movie spoilers on TikTok social media, with a case study of the film Mencuri Raden Saleh. The phenomenon of movie spoilers on social media is a problem that impacts the economic and moral rights of creators of cinematographic works. This study uses a sociological, legal approach to understand the interaction of society with applicable legal norms. The study results indicate that TikTok's policies are not yet in line with copyright protection regulations in Indonesia, so copyright infringement in the form of spoilers and film piracy is still difficult to control. Although Law Number 28 of 2014 has provided legal protection for copyright holders, its implementation is still hampered by the nature of the complaint offense, which requires copyright owners to file a report first so that the legal process can run. In addition, the low public legal awareness of copyright is also a significant factor in the rampant practice of movie piracy on social media. Therefore, a more comprehensive regulatory update is needed, as increased supervision of digital platforms and wider socialization to raise public awareness of the importance of copyright protection in the digital era.